Oncogenic p95HER2 regulates Na+-HCO3- cotransporter NBCn1 mRNA stability in breast cancer cells via 3'UTR-dependent processes - Gorbatenko, Andrej; Olesen, Christina W; Loebl, Nathalie; Sigurdsson, Haraldur H; Bianchi, Carolina; Pedraz-Cuesta, Elena; Christiansen, Jan; Pedersen, Stine Falsig (Biochemical journal, 2016)
The Na -HCO cotransporter NBCn1 (SLC4A7) is up-regulated in breast cancer, important for tumor growth, and a single nucleotide polymorphism (SNP), rs4973768, in its 3' untranslated region (3'UTR) correlates with increased breast cancer risk. We previously demonstrated that NBCn1 expression and promoter activity are strongly increased in breast cancer cells expressing a constitutively active oncogenic human epidermal growth factor receptor 2 (HER2) (p95HER2). Here, we address the roles of p95HER2 in regulating NBCn1 expression via post-transcriptional mechanisms. p95HER2 expression in MCF-7 cells reduced the rate of NBCn1 mRNA degradation. The NBCn1 3'UTR down-regulated luciferase reporter expression in control cells, and this was reversed by p95HER2, suggesting that p95HER2 counteracts 3'UTR-mediated suppression of NBCn1 expression. Truncation analyses identified three NBCn1 3'UTR regions of regulatory importance. Mutation of putative miRNA-binding sites (miR-374a/b, miR-200b/c, miR-29a/b/c, miR-488) in these regions did not have significant impact on 3'UTR activity. The NBCn1 3'UTR interacted directly with the RNA-binding protein human antigen R (HuR), and HuR knockdown reduced NBCn1 expression. Conversely, ablation of a distal AU-rich element increased 3'UTR-driven reporter activity, suggesting complex regulatory roles of these sites. The cancer-associated SNP variant decreased reporter expression in T-47D breast cancer cells, yet not in MCF-7, MDA-MB-231 and SK-BR-3 cells, arguing against a general role in regulating NBCn1 expression. Finally, p95HER2 expression increased total and plasma membrane NBCn1 protein levels and decreased the rate of NBCn1 protein degradation. Collectively, this is the first work to demonstrate 3'UTR-mediated NBCn1 regulation, shows that p95HER2 regulates NBCn1 expression at multiple levels, and substantiates the central position of p95HER2-NBCn1 signaling in breast cancer.